1994
DOI: 10.1021/bi00195a008
|View full text |Cite
|
Sign up to set email alerts
|

Role of methionine 230 in intramolecular electron transfer between the oxyferryl heme and tryptophan 191 in cytochrome c peroxidase compound II

Abstract: The kinetics of electron transfer from cytochrome c (CC) to yeast cytochrome c peroxidase (CcP) compound I were studied by flash photolysis and stopped-flow spectroscopy. Flash photolysis studies employed horse C C derivatives labeled at specific lysine amino groups with (dicarb0xybipyridine)bis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 33 publications
5
77
2
Order By: Relevance
“…It has been shown that methionine residues play a role in the electrostatic stabilization of Trp protein radicals 47,25,62,[66][67][68] .…”
Section: Lret Pathway/s In Aaudypmentioning
confidence: 99%
“…It has been shown that methionine residues play a role in the electrostatic stabilization of Trp protein radicals 47,25,62,[66][67][68] .…”
Section: Lret Pathway/s In Aaudypmentioning
confidence: 99%
“…However, this simple picture became clouded with more detailed studies and it was found that with yeast cytc the activity actually increases with increasing ionic strength and only at moderately high salt concentrations does the activity decrease [77]. The reason for such behavior may be related to a change in rate limiting step as a function of ionic strength [56] and to best understand this explanation we refer to the following scheme fashioned after [78]. …”
Section: Electron Transfermentioning
confidence: 99%
“…All of the Ru-Cc derivatives were found to initially reduce the Trp-191 radical cation in CMPI(Fe IV d O,R •+ ) as shown in Scheme 1 (18,19). CMPII(Fe IV dO,R) is then converted to CMPII(Fe III ,R •+ ) by intramolecular electron transfer, followed by reduction of the radical cation in CMPII(Fe III ,R •+ ) by a second molecule of Cc II which gives the resting enzyme (21). Stopped-flow studies have demonstrated that native hCc and yCc initially reduce the radical cation in CMPI according to Scheme 1 under all conditions of ionic strength and pH (22,24,25).…”
mentioning
confidence: 99%